Identification and cloning of genes involved in phaseolotoxin production by Pseudomonas syringae pv. "phaseolicola". - Peet, R C (1986)
Genes involved in the production of phaseolotoxin by Pseudomonas syringae pv. "phaseolicola" NPS3121 were identified by Tn5 mutagenesis and cosmid cloning. A total of 5,180 kanamycin-resistant colonies were screened for the loss of phaseolotoxin production by a microbiological assay. Six independent, prototrophic, Tox- mutants were isolated that had Tn5 insertions in five different EcoRI fragments. All six mutants had Tn5 inserted in the same KpnI fragment, which had a length of ca. 28 kilobases including Tn5. The mutants produced residual toxin in vitro. An EcoRI fragment containing Tn5 and flanking sequences from mutant NPS4336 was cloned and used to probe a wild-type genomic library by colony hybridization. Seven recombinant plasmids showing homology to this probe were identified. Each Tox- mutant was restored in OCTase-specific toxin production by two or more of the recombinant plasmids. The data suggest that at least some of the genes involved in phaseolotoxin production were clustered in a large KpnI fragment. No homology was detected between the Tn5 target fragment cloned from mutant NPS4336 and the total genomic DNA from closely or distantly related bacteria that do not produce phaseolotoxin.